Assessment of biochar, bio-oil and biogas production from lemon myrtle waste via microwave assisted catalytic pyrolysis using CaO based catalyst and zeolite catalyst - Muhammad W.Z.W.; Isa M.R.; Habib S.H.; Seah C.C.; Hafriz R.S.R.M.; Shamsuddin A.H. (Elsevier Ltd, 2024)
This work fashioned the conventional pyrolysis by introducing a microwave process to assess the feasibility of lemon myrtle waste (LMW) to produce biochar, bio-oil and biogas in the presence of catalyst. Microwave assisted pyrolysis (MAP) of LMW was established as a control before introducing five different catalysts in the Microwave Assisted Catalytic Pyrolysis (MACP) reaction. The catalyst includes CaO based catalyst (Dolomite and Eggshell (CES)) and Zeolite based catalyst (ZSM-5, HY-Zeolites and FCC). These catalysts were characterized using the X-Ray Diffraction (XRD) method, Brunauer-Emmet-Teller (BET) surface area, Particle Size Analyzer (PSA) and Scanning Electron Microscope (SEM) to determine their physical properties. These characterizations proved that all catalysts are suitable for the MACP reaction. The biochar, bio oil and biogas yield were determined using mass balance. Biochar quality was evaluated by its calorific value content while the bio-oil and biogas produced from the MACP was characterized using Gas Chromatography-Mass Spectrometry (GCMS) and GC-Thermal Conductivity Detector (GC-TCD) analysis. The result shows that more than 95 % of MACP yield were biochar and biogas. MAP of LMW produced highest calorific value biochar at 21.72 MJ/kg. Dolomite catalyst produced the highest bio-oil yield of 2.27 % with the highest hydrocarbon content of 86.35 %. MACP of LMW proved that the bio-oil yield produced was increase by 0.7 % while hydrocarbon percentage was increased by 11.4 % in the presence of Dolomite catalyst. The feasibility of LMW to be used as solid fuel is successfully proven form this study. 2023 The Author(s)